Urinary iodine concentration and thyroid function in pregnant women with hypertensive disorders - Queiroz, Adriana Duarte Miranda; Torres, Maria Roseneide dos Santos; Ratis, Luana Cristina Fernandes; Morais, Maria Clara Vieira; Figueiroa, José Natal; Souza, Alex Sandro Rolland (Frontiers in Endocrinology, 2025)
Pregnant women are considered a risk group for iodine deficiency, and this condition may be associated with changes in thyroid hormone levels and an increased risk of developing hypertensive disorders.ObjectiveTo assess urinary iodine concentration (UIC), thyroid-stimulating hormone (TSH) and anti-thyroid peroxidase (TPO) antibody levels in pregnant women with hypertensive disorders.MethodsThis cross-sectional study was conducted in a referral maternity hospital in Paraíba, Brazil between June 2022 and April 2023. A total of 250 women over 18 years of age, in the third trimester of pregnancy and diagnosed with hypertensive disorders were included. Clinical and epidemiological data, as well as TSH, anti-TPO antibodies and UIC were assessed. Iodine deficiency was defined as UIC levels <150 μg/L. Correlations between UIC and the study variables were analyzed using regression models adjusted with the cenreg function of the Nondetects and Data Analysis for Environmental Data (NADA) statistical package.ResultsThe median UIC was 82.5 μg/L (95%CI: 72.9–93.8), with 76.4% of participants (n=191) being iodine deficient. UIC differed among hypertensive disorders (p=0.023), with significant differences found between gestational hypertension (111.6 μg/L) and both preeclampsia (61.3 μg/L; p=0.018) and superimposed preeclampsia (70 μg/L; p=0.020). Systolic blood pressure (SBP) and gestational age correlated negatively with UIC (-0.006±0.002, p=0.015; -0.03±0.01, p=0.042, respectively). No correlation was found between UIC and TSH levels or anti-TPO antibodies.ConclusionLower UIC levels were observed in pregnant women with pre-eclampsia or superimposed pre-eclampsia compared to women with gestational hypertension, as well as in higher SBP levels and gestational age. Detection of iodine deficiency in pregnancy may help identify women at higher risk of hypertensive complications, and supplementation may potentially improve outcomes.